Microwave-Assisted Nickel-Catalyzed Synthesis of Benzimidazoles: Ammonia as a Cheap and Nontoxic Nitrogen Source - Ke, Fang; Zhang, Peng; Xu, Yiwen; Lin, Xiaoyan; Lin, Jin; Lin, Chen; Xu, Jianhua (Synlett, 2018)
An efficient and convenient Ni-catalyzed C–N bond formation for the synthesis of various benzimidazoles from various 2-haloanilines, aldehydes, and ammonia in a concise manner is reported. This protocol uses commercially available, nonhazardous, clean ammonia as a reaction partner instead of other nitrogen sources. Benzimidazoles, as the sole products, were obtained in high to excellent yields (up to 95%).
Keywords: nickel catalysis; C–N bond formation; benzimidazoles; microwave heating; ammonia